THE ROLE OF ORGANIC FERTILIZERS IN INCREASING BARLEY YIELD - Mukhlisa Soipova (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This study examines the role of organic fertilizers in enhancing barley yield. With the increasing demand for sustainable agricultural practices, organic fertilizers offer an eco-friendly alternative to synthetic chemicals. The research highlights the positive impact of organic fertilizers on soil health, nutrient availability, and barley growth. Field trials were conducted to compare the effect of organic fertilizers such as compost, manure, and green manure on barley yield. The results indicate that organic fertilizers significantly improve barley productivity by enhancing soil structure, promoting microbial activity, and increasing nutrient content. This study emphasizes the importance of integrating organic fertilizers in barley cultivation for sustainable farming and higher yields.